Medication adherence in Jordanian patients with multimorbidity: a cross-sectional mixed-methods study in outpatient clinics - Abed, Anas; Abu Assab, Mohammad; Abu Dayyih, Wael; Alotaibi, Badriyah S.; Alsubaie, Nawal (Frontiers in Pharmacology, 2025)
BackgroundMultimorbidity, the coexistence of two or more chronic conditions, is increasingly prevalent in Jordan, a middle-income country with a growing non-communicable disease (NCD) burden and limited data on medication adherence. This study examined adherence prevalence, predictors, and barriers among Jordanians with multimorbidity to inform interventions supporting Sustainable Development Goal 3.MethodsA cross-sectional, mixed-methods study was conducted from April to December 2024 in two tertiary Hospitals’ outpatient clinics in Amman. Adults (≥18 years) with ≥2 chronic conditions requiring ongoing medication (n = 405) were recruited via convenience sampling. Adherence was assessed using the General Medication Adherence Scale (GMAS, 0–33; high adherence defined as GMAS ≥27) alongside a Self-Administered Comorbidity Questionnaire (SCQ)-like checklist. Qualitative data were collected through an open-ended question and analyzed using thematic analysis. Descriptive statistics, correlation analysis, and logistic regression were used. Qualitative data were analysed using thematic analysis.ResultsOf 420 invited participants, 405 completed the survey (response rate: 96.4%). High adherence (GMAS ≥27) was observed in 54.3% of participants. Factors positively associated with medication adherence included older age, higher income, fewer medications, higher health literacy, and social support, while cost, polypharmacy, forgetfulness, rural residence, and low perceived medication necessity were key barriers. Six qualitative themes were identified: economic strain, access gaps, cultural beliefs, religious coping, caregiving burden, and symptom management issues.ConclusionThis first study of medication adherence in Jordanian multimorbidity highlights actionable barriers and facilitators, offering a scalable model for resource-limited settings. Subsidies, mobile pharmacies, and culturally tailored strategies could substantially reduce the non-adherence rates, advancing NCD control regionally and globally.